(3fXQjI GdefXeI (B:s (3eONd GdJUeje (B/s - (3GdNaGLj, fYeI YHGSs; (3GdZGdHj, WGgQ eMSf s ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2009)
(3eONd YGe aj OQGSI GdefXeI h GdJfXje , HjFI GdefXeI h CUMGH GdeUGdM h GdGNdGb , JUeje GdefXeIh JUeje GdJQcjH GdJfXjej , GdYhGed GdehbajI GdeDKQI Ydi CHYGO Gdgjcd GdJfXjej h NUGFUg(B.s
(3eQGLY U(B.173 ((3GbJfGAGJ (B2014 3(3f(B)s
Keywords: (3GdJfXjes; (3GdefXeGJs